Development of a beach cleaning machine / Muhammad Syahir Mohamad Tazri and Wan Muhammad Syahmi Wan Fauzi - Mohamad Tazri, Muhammad Syahir; Wan Fauzi, Wan Muhammad Syahmi (School of Mechanical Engineering, 2022)
Beaches used to be a fun place to go since there are many activities to do. People used to go to beaches to heal themselves by chilling with nature. Nowadays, there are a lot of beaches that have been polluted by irresponsible people who throw rubbish on the beach. There are a lot of technologies that have been innovated such as beach cleaning machines. This machine helps people to clean beaches very effectively since it can save more time and energy. The project is made in Final Year Project 2 (FYP2) is the adjustment and improvement of the current product in terms of size and price. Designing the beach cleaning machine using the state-of-art SolidWorks 2021 and fabricating the beach cleaning machine as a proof of concept are the main objectives of this FYP 2. The methodology used to fabricate this product is Morphological chart and Pugh chart. The product is to make people at the beach like to clean the beach since it is suitable to use by them. In conclusion, one of the objectives of this project is achieved since there are the designs of beach cleaning machines using SolidWorks 2021.